2017
DOI: 10.1039/c7cp03146g
|View full text |Cite
|
Sign up to set email alerts
|

Supersaturation dependence of glycine polymorphism using laser-induced nucleation, sonocrystallization and nucleation by mechanical shock

Abstract: The nucleation of glycine from aqueous supersaturated solution has been studied using nonphotochemical laser-induced nucleation (NPLIN), ultrasound (sonocrystallization), and mechanical shock of sample vials. It was found that at higher supersaturation, samples were more susceptible to nucleation and produced more of the g-glycine polymorph. The results are described in terms of a mechanism common to all three nucleation methods, involving the induction of cavitation events and pressure shockwaves. The switch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 59 publications
6
63
2
Order By: Relevance
“…A repeat of these experiments in the bulk would be worthwhile, bearing in mind the possibility of a hidden liquidliquid critical point enhancing concentration fluctuations. Bulk non-photochemical laser-induced nucleation (NPLIN) phenomena described by Garetz, Alexander, and others [1][2][3][4][5][6][7][8][9][10][11][12][13][14]75,76 fit with our narrative as the final states have higher refractive indices than their precursor mixtures. There are two potential exceptions to this picture, the first being laser-induced bubble nucleation.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A repeat of these experiments in the bulk would be worthwhile, bearing in mind the possibility of a hidden liquidliquid critical point enhancing concentration fluctuations. Bulk non-photochemical laser-induced nucleation (NPLIN) phenomena described by Garetz, Alexander, and others [1][2][3][4][5][6][7][8][9][10][11][12][13][14]75,76 fit with our narrative as the final states have higher refractive indices than their precursor mixtures. There are two potential exceptions to this picture, the first being laser-induced bubble nucleation.…”
Section: Discussionsupporting
confidence: 72%
“…1 Most excitingly, it was reported that the laser polarisation could be used to control which polymorph would nucleate, promising an unprecedented degree of control. 2,3 Subsequent work showed that laser pulses can induce nucleation of various crystals, [4][5][6][7][8] liquid crystals 9,10 and bubbles. 11 However, these nanosecond-laser nucleation experiments defied all explanation.…”
Section: Introductionmentioning
confidence: 99%
“…-Glycine is obtained directly from aqueous solution. The -form has been obtained using a number of different methods including laser-assisted nucleation (Sun et al, 2006;Liu et al, 2017) and slow crystallization from a basic solution, but can also be obtained directly from aqueous solution in the case of the deuterated isotopologue (Hughes & Harris, 2009). -Glycine is obtained by the addition of methanol/ethanol to a saturated glycine solution (Weissbuch et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1 Most excitingly, it was reported that the laser polarization could be used to control which polymorph would nucleate, promising an unprecedented degree of control. 2,3 Subsequent work showed that laser pulses can induce nucleation of various crystals, [4][5][6][7][8] liquid crystals, 9,10 and bubbles. 11 However, these nanosecond-laser nucleation experiments defied all explanation.…”
Section: Introductionmentioning
confidence: 99%